Current approach to diagnosis and treatment for liver failure (literature review) - A. N. Plekhanov; A. I. Tovarshinov (Acta Biomedica Scientifica, 2016)
Currently, the world is marked rise in the number of patients with liver disease. Approximately 100,000 patients hepatitis complicated by acute liver failure, with mortality in this disease reaches 70-90 % despite the use of modern methods of treatment Currently, there are more than 20 concepts of this disease. In 15-20 % of cases the cause of acute liver failure can not be established. Most clinicians believe that the pathogenesis of liver failure is a strong humoral and hyperimmune response, resulting in massive necrosis of liver cells. Diagnosis of liver failure based on anamnesis, clinical, biochemical and electroencephalographic changes. Traditional conservative therapy of acute liver failure in the first place based on the measures taken to address the etiological factor. Transplantation is an effective measure in acute liver failure. In the world there are a sufficient number of prognostic scales, criteria and risk factors of acute liver failure. Each of them has its own characteristics, but a unified system of prognostic estimation of arrester.